Percakapan Konseling dengan Masyarakat Akar Rumput (Termarjinalkan) di Kota Manado - Nendissa, Julio Eleazer; Sureni, Sureni; Manusiwa, Ceril Maria; Kowal, Jeniar Rainhard (Jurnal PKM Setiadharma, 2025)
Marginalised communities in Manado often face multifaceted challenges—economic, social, cultural, and spiritual—that restrict their access to basic rights and hinder personal development. Counselling conversations are introduced as a holistic intervention, addressing not only material needs but also emotional and spiritual dimensions. This approach aims to enhance critical awareness, build individual resilience, and foster spaces for healing and empowerment. Combining participatory and contextual methods, it involves the community actively in the counselling process while adapting interventions to their specific realities. Techniques include in-depth interviews, group discussions, and collaborative reflection to identify issues and co-create solutions. Findings show marked improvements in participants’ self-confidence, critical thinking, and capacity to initiate social change. Enhanced interpersonal relationships and a renewed sense of meaning in life further support their journey out of marginalisation. Counselling thus emerges as both a spiritual support mechanism and a transformative tool for inclusive community empowerment.